Comparison of group and individual cognitive-behavioral therapy for patients with bulimia nervosa. - Chen, E; Touyz, S; Beumont, P; Fairburn, C; Griffiths, R; Butow, P; Russell, J; Schotte, D; Gertler, R; Basten, C (2003)
OBJECTIVE: The clinical effectiveness of group and individual cognitive-behavioral therapy (CBT) for bulimia nervosa (BN) was compared. METHOD: Sixty BN patients from hospitals and general practitioners in Sydney, Australia, were allocated randomly to group or individual CBT. Forty-four completed treatment (n = 22 in group CBT and n = 22 in individual CBT). Patients were assessed at pretreatment, posttreatment, and at 3 and 6 months follow-up with the Eating Disorder Examination-12 and self-report questionnaires examining weight and shape attitudes (Eating Disorder Inventory-2), social adjustment (Social Adjustment Scale-Modified), self-esteem (Rosenberg Self-Esteem Scale), and general psychopathology (Symptom Checklist 90R). RESULTS: The effects of group and individual CBT were equivalent on most measures. However, a significantly greater proportion of individual CBT patients than group CBT patients were abstinent from bulimic behaviors at posttreatment, but not at follow-up. DISCUSSION: This has implications for the delivery of cost-effective and clinically effective treatment for BN.